Clinical Characteristics Associated with Suicide Attempts in Clinical Settings: A Comparison of Suicidal and Non-Suicidal Depressed Inpatients - Gramaglia, Carla; Feggi, Alessandro; Bergamasco, Paola; Bert, Fabrizio; Gattoni, Eleonora; Marangon, Debora; Siliquini, Roberta; Torre, Eugenio; Zeppegno, Patrizia (Frontiers in Psychiatry, 2016)
Introduction Both psychiatrists and psychiatric nurses are involved in the psychiatric management of suicidal inpatients. One-to-one observation by qualified nurses and the accommodation of the patient in a room close to the infirmary are usually recommended. Suicidal risk should be reassessed periodically to check response to treatment. Aim To compare the severity of depressive symptoms in depressed inpatients admitted after an attempted suicide and those admitted for any other reason and to assess the severity of suicide attempts and the management of suicidal risk in clinical settings. Materials and methods We divided the sample into two subgroups: patients with a diagnosis of depression admitted because of a recent suicide attempt and depressed patients with no recent history of attempted suicide. Socio-demographic and clinical data were gathered; assessments included the Montgomery-Asberg Depression Rating Scale and the Nurses’ Global Assessment of Suicide Risk (NGASR). Results Forty-six patients were recruited over a 1-year period: 20 were admitted to the hospital following a suicide attempt; the other 26 had not attempted suicide and were admitted for other depression-related reasons. Multivariate analysis revealed a correlation between use of antidepressants and recent attempted suicide. Attempting suicide was not related to the severity of depressive symptoms. In the recent suicide attempt subgroup, NGASR suicide risk levels were lower at discharge than at admission. Patients with a recent history of attempted suicide had a higher number of suicide attempts in their clinical history than patients with no recent history of attempted suicide. Conclusion There were no correlations between psychiatric diagnosis, severity of depressive symptoms, and recent suicide attempt. Antidepressant therapy protected against suicide attempts. History of suicide attempts was one of the best predictors of recent attempted suicide. A more thorough understanding of the complex phenomenon of suicide and the reasons for suicidal behavior is needed.